2021
DOI: 10.3892/br.2021.1432
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxymatrine on liver gluconeogenesis is associated with the regulation of PEPCK and G6Pase expression and AKT phosphorylation

Abstract: An increase in liver gluconeogenesis is an important pathological phenomenon in type 2 diabetes mellitus (T2DM) and oxymatrine is an effective natural drug used for T2DM treatment. The present study aimed to explore the effect of oxymatrine on gluconeogenesis and elucidate the underlying mechanism. Male Sprague-Dawley rats were treated with a high-fat diet and streptozotocin for 4 weeks to induce T2DM, and HepG2 cells were treated with 55 mM glucose to simulate T2DM in vitro. T2DM rats were treated with oxymat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…PEPCK is an important kinase in gluconeogenesis. Early research demonstrated that increased PEPCK is a common response to environmental stress [56], which converts non-sugar substances (glycerin, lactic acid, and glycogenic amino acids) into glucose to cope with stress [57]. Consistently, in the current study, as the Se supplementation increases, the sarcous PEPCK shows a decreasing trend under CHS.…”
Section: Discussionsupporting
confidence: 86%
“…PEPCK is an important kinase in gluconeogenesis. Early research demonstrated that increased PEPCK is a common response to environmental stress [56], which converts non-sugar substances (glycerin, lactic acid, and glycogenic amino acids) into glucose to cope with stress [57]. Consistently, in the current study, as the Se supplementation increases, the sarcous PEPCK shows a decreasing trend under CHS.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies found that OMT can mediate its function in various physiological and pathological processes through the AKT signaling pathway, including liver gluconeogenesis, breast cancer, hypoxic-ischemic brain damage and cardiomyocyte injury [39][40][41][42]. Our in vitro experiments also support the hypothesis that OMT treatment can restore radiosensitivity to inhibit irradiation-induced EMT, invasion and migration in NSCLC cells through the DcR3/AKT/GSK-3β pathway.…”
Section: P R E P R I N Tsupporting
confidence: 86%
“…The liver is the central platform for the metabolism of blood glucose and fatty acids in the body and plays an important role in the metabolism of carbohydrates, 37 regulating gluconeogenesis in the organism and being responsible for the balance of blood glucose. Gluconeogenesis is an important pathway for producing glucose from lactate, amino acid, and glycerol in the liver or kidneys, to ensure the homeostasis of blood glucose levels, 38 its occurrence is regulated by insulin and glucagon 39 and also by a series of transcription factors that feed signals to two key rate-limiting enzymes of gluconeogenesis: G6Pase and PCK1. 40 Natural products have shown significant potential in modulating and activating the AMPK pathway.…”
Section: Discussionmentioning
confidence: 99%